An in vitro chondro-osteo-vascular triphasic model of the osteochondral complex. (May 2021) - Pirosa, Alessandro; Gottardi, Riccardo; Alexander, Peter G.; Puppi, Dario; Chiellini, Federica; Tuan, Rocky S.
Abstract: The generation of engineered models of the osteochondral complex to study its pathologies and develop possible treatments is hindered by the distinctly different properties of articular cartilage and subchondral bone, with the latter characterized by vascularization. In vitro models of the osteochondral complex have been mainly engineered as biphasic constructs containing just cartilage and bone cells, a condition very dissimilar from the in vivo environment. The different cellular components of the osteochondral complex are governed by interacting biochemical signaling; hence, to study the crosstalk among chondrocytes, osteoblasts, and endothelial cells, we have developed a novel triphasic model of the osteochondral tissue interface. Wet-spun poly(ε-caprolactone) (PCL) and PCL/hydroxyapatite (HA) scaffolds in combination with a methacrylated gelatin (gelMA) hydrogel were used as the polymeric backbone of the constructs. The scaffold components were engineered with human bone marrow derived mesenchymal stem cells (hMSCs) and human umbilical vein endothelial cells (HUVECs), and differentiated using a dual chamber microphysiological system (MPS) bioreactor that allows the simultaneous, separate flow of media of different compositions for induced differentiation of each compartment towards a cartilaginous or osseous lineage. Within the engineered Microphysiological Vascularized Osteochondral System, hMSCs showed spatially distinct chondrogenic and osteogenic markers in terms of histology and gene expression. HUVECs formed a stable capillary-like network in the engineered bone compartment and enhanced both chondrogenic and osteogenic differentiation of hMSCs, resulting in the generation of an in vitro system that mimics a vascularized osteochondral interface tissue.